Four Policy Actions to Improve Local Governance of the Oil and Gas Sector - Patricia I. Vasquez (Revue Internationale de Politique de Développement)
Increasing natural resource revenues at the sub-national government level does not necessarily guarantee that they will be well spent. This article uses examples from Latin America and East Africa to discuss four actions that can contribute to a more equitable and efficient use of oil and gas resources at the local level. It also analyses the challenges in implementing them. Ultimately, the author argues that an efficient and equitable use of hydrocarbons resources at the sub-national level is largely related to the political and economic interactions between the federal and local governments.